A Systematic Process to Facilitate Evidence-Informed Decisionmaking Regarding Program Expansion The RAND Toolkit, Volume 3 - Martin, Laurie T. (RAND Corporation, 2014)
Despite supporting more than 200 psychological health and traumatic brain injury programs, the Department of Defense lacks a way to develop, track, and assess the performance of this portfolio. RAND researchers developed a potential model and tools to support a centralized, systematic, and ongoing process to aid in making decisions around continued program support and expansion.